ADVANCED CHATBOT DEVELOPMENT TO IMPROVE STUDENT LITERACY AND NUMERACY SKILLS - Faqih, Muhammad Izzatul; Adriyani, Zuanita; Listiyani, Laily (Phenomenon : Jurnal Pendidikan MIPA, 2022)
The literacy and numeracy skills of prospective teacher students are still in the very low category. This is an indication that the opportunity to increase students' literacy and numeracy skills is still very high. The purpose of this study was to measure the increase in literacy and numeracy in science learning using the Advanced Chatbot media. This type of research is an experimental research with a pretest-posttest group design technique. The research was conducted at the students of Elementary School Teacher Education, Walisongo State Islamic University, Semarang and University of Sarjanawiyata Tamansiswa Yogyakarta, with a total of 57 students. The data acquisition technique used a test instrument. The literacy and numeracy indicators used are based on the achievements developed by PISA 2015 namely knowledge and skills to 1) use various numbers and symbols related to basic mathematical concepts to solve practical problems in various contexts of everyday life; and 2) analyze the information displayed in the form of graphs, tables, and charts. Then use the interpretation of these results to predict and make decisions. The test instrument was declared valid as seen from the level of difficulty and the suitability of the items. The results of the analysis show the mean value of n-Gain is 0.32 in the medium category. This means that there is an increase in student literacy and numeracy in science learning assisted by advanced chatbot media. In conclusion, advanced chatbots can be used as an alternative media for science learning which can effectively improve students' literacy and numeracy skills.